Judicial review in an objective legal system : Tara Smith, University of Texas, Austin. - Smith, Tara, 1961- (Cambridge University Press, 2015)
How should courts interpret the law? While all agree that courts must be objective, people differ sharply over what this demands in practice: fidelity to the text? To the will of the people? To certain moral ideals? In Judicial Review in an Objective Legal System, Tara Smith breaks through the false dichotomies inherent in dominant theories - various forms of originalism, living constitutionalism, and minimalism - to present a new approach to judicial review. She contends that we cannot assess judicial review in isolation from the larger enterprise of which it is a part. By providing careful clarification of both the function of the legal system as well as of objectivity itself, she produces a compelling, firmly grounded account of genuinely objective judicial review. Smith's innovative approach marks a welcome advance for anyone interested in legal objectivity and individual rights.